TANTANGAN DAN PROBLEMATIKA PENDIDIKAN ISLAM DI ERA GLOBALISASI - Sukari; Fadhilah Wardatul Muslimah; Fatimah Az Zahrah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Globalization has brought significant changes to various aspects of human life, including education. Islamic education, which is oriented toward the development of character, spirituality, and intellectual capacity, faces numerous challenges in the era of globalization, such as the influence of foreign cultures, rapid digital transformation, and the demands of 21st-century competencies. This study aims to examine the challenges, problems, and impacts of globalization on Islamic education, as well as to formulate relevant modernization strategies. This research employs a library research method by analyzing books and recent scholarly articles. The findings indicate that Islamic education encounters both internal and external challenges, including weak curriculum integration, limited teacher competence, and a crisis of moral values and identity among students. Nevertheless, globalization also provides opportunities for innovation in learning and the enhancement of educational quality through the effective use of technology and human resource development. Therefore, Islamic education must be adaptive and innovative while consistently maintaining Islamic values in order to produce Muslim generations who are faithful, morally upright, knowledgeable, and capable of contributing positively to the global society.